Pharmacy practice in developing countries : achievements and challenges - Fathelrahman, Ahmed Ibrahim; Mohamed Izham Mohamed Ibrahim; Wertheimer, Albert I. (Elsevier, 2016)
Pharmacy Practice in Developing Countries: Achievements and Challenges offers a detailed review of the history and development of pharmacy practice in developing countries across Africa, Asia, and South America. Pharmacy practice varies substantially from country to country due to variations in needs and expectations, culture, challenges, policy, regulations, available resources, and other factors. This book focuses on each country's strengths and achievements, as well as areas of weakness, barriers to improvement and challenges. It sets out to establish a baseline for best practices, taking all of these factors into account and offering solutions and opportunities for the future. This book is a valuable resource for academics, researchers, practicing pharmacists, policy makers, and students involved in pharmacy practice worldwide as it provides lessons learned on a global scale and seeks to advance the pharmacy profession.--